2020
DOI: 10.1186/s12864-020-6595-z
|View full text |Cite
|
Sign up to set email alerts
|

New genome assemblies reveal patterns of domestication and adaptation across Brettanomyces (Dekkera) species

Abstract: Background: Yeasts of the genus Brettanomyces are of significant interest, both for their capacity to spoil, as well as their potential to positively contribute to different industrial fermentations. However, considerable variance exists in the depth of research and knowledgebase of the five currently known species of Brettanomyces. For instance, Brettanomyces bruxellensis has been heavily studied and many resources are available for this species, whereas Brettanomyces nanus is rarely studied and lacks a publi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 87 publications
2
19
0
Order By: Relevance
“…Proteomes of A. robustus (NCBI taxid 1754,192), P. finnis (taxid 1754191), Neocallimastix californiae (1754190), Sch. japonicus (402676), D. bruxellensis (5007; [ 91 ]), K. marxianus (1003335) and O. parapolymorpha (871575) were subjected to protein blast search in NCBI [ 92 ], using LkUra1 (UniProt KB accession number Q7Z892) and LkUra9 (Q6V3W9) as queries and applying default settings. Similarly, the proteomes of A. robustus , P. finnis , N. californiae , Sch.…”
Section: Methodsmentioning
confidence: 99%
“…Proteomes of A. robustus (NCBI taxid 1754,192), P. finnis (taxid 1754191), Neocallimastix californiae (1754190), Sch. japonicus (402676), D. bruxellensis (5007; [ 91 ]), K. marxianus (1003335) and O. parapolymorpha (871575) were subjected to protein blast search in NCBI [ 92 ], using LkUra1 (UniProt KB accession number Q7Z892) and LkUra9 (Q6V3W9) as queries and applying default settings. Similarly, the proteomes of A. robustus , P. finnis , N. californiae , Sch.…”
Section: Methodsmentioning
confidence: 99%
“…They highlight, for the first time, the key role of yeasts and their metabolisms in terms of invertase activity and the fermentation capacity, which can differ, depending on yeast strains ( Table 1 ). Bibliographic resources and the NCBI database have reported the existence of genes encoding invertase in S. cerevisiae (internal and extracellular enzyme) [ 53 , 54 , 55 , 56 ] and B. bruxellensis (internal and extracellular enzyme) [ 57 , 58 , 59 , 60 ], but few data is available for H. valbyensis . However, genomic studies on the Hanseniaspora genus reported the loss of the SUC gene of the branch to which H. valbyensis belongs, thus supporting the low sucrose hydrolysis observed ( Table 1 ) [ 61 ].…”
Section: Resultsmentioning
confidence: 99%
“…In its sexual form, it is also referred to as Dekkera, a genus comprising the most frequently found species Dekkera/Brettanomyces bruxellensis and Dekkera/Brettanomyces anomalus (for review, see Smith, 2011). In addition, other asexual species of Brettanomyces have been described, such as Brettanomyces naardenensis, Brettanomyces custersianus, and Brettanomyces nanus (Kurtzman et al, 2011;Tiukova et al, 2019;Roach and Borneman, 2020). The potential of Brettanomyces species for brewing is controversial, as it is usually recognized as a spoilage yeast, being the cause of major economic losses in many production facilities (Gilliland, 1961;Lebleux et al, 2020).…”
Section: Introductionmentioning
confidence: 99%